(untitled) (مجلة الواحات للبحوث والدراسات, 2015)
One of the goals that the bank seeks to achieve higher levels of profitability, and this can only be done by reducing potential losses as much as possible (including from the risk of financial deficit) at the same time maintaining the safety of the banking through its compliance with various financial indicators. Accordingly, we find that the bank struggling to reduce the risk of fianacial deficit, and it strives to raise the solvency ratio. This study aims to identify the impact of the capital of risk under the Basel Committee to reduce the financial deficit through ratios for sample analysis Arab banks during the study period 2006 - 2010 based on informations extracted from the annual reports of these banks, and we came in this study that the capital of risk affect the deficit loans and has a role in reducing them, as the increase inthe bank’s capital adequacy affect loans Troubled banking and contribute to reduction;but not permanently there may be other factors to the reduction of deficit loans Key words : The capital of risk, deficit loans, Basel I ,Basel II